Manajemen Organisasi Pers Mahasiswa dalam Reportase - Alfian, Alif Muhamad; suherdiana, dadan; Rusmulyadi, Rusmulyadi (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
The existence of the student press for each generation always depicts an interesting story in playing an active role in society. This research aims to find out how the management of student press organizations at UKM Perslima (POAC) in reporting activities without a communication background. This study uses a qualitative approach, data collection is done by interview and observation techniques. The results of the Perslima UKM research carried out the planning stages consisting of the editorial meeting agenda, the validity of the news urgency. the organizing stage starts from managing prospective members, dividing the coverage team, giving jobdesk program coverage. the implementation stage is upgrading in provision of supplies, implementation of coverage content, standardization of technical coverage. the supervision stage is carried out by monitoring members, implementing evaluation forums, responding to news viewers, providing motivation in the form of appreciation/holding special activities.